1986
DOI: 10.1139/b86-142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tree age and growth rate on the radial resin duct system in loblolly pine (Pinus taeda)

Abstract: Formation of radial resin ducts and their associated secretory cells in loblolly pine (Pinus taeda L.) is influenced by the age and growth rate of the annual ring in which the ducts are formed. The spatial pattern of radial ducts on the tangential plane is nonrandom, exhibiting a regular or dispersed pattern. A significantly higher density of radial ducts was found in the inner, first-formed growth rings at all heights within the tree. Radial duct formation was found to be positively correlated with radial gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…A relationship between the composition and production of oleoresin and water stress (Hodges and Lorio, 1975;Hodges et al, 1979; among others) may explain why oleoresin production is greater in thinned than unthinned loblolly pine stands (Brown et al, 1987). DeAngelis et al (1986) reported that age and rate of radial growth influenced the formation and development of radial resin ducts, which may explain why decreased radial tree growth and southern pine beetle infestations are correlated (Coulson et al, 1974). Hodges et al (1979) compared the chemical and physical properties of the oleoresin in four pine species, loblolly, shortleaf, P. echinata Mill., slash, P. elliottii Engelm., and longleaf pines, P. palustris Mill., and concluded there were differences in their relative susceptibility that were best explained by differences in resin flow characteristics.…”
Section: Tree and Stand Factors Associated With Southern Pine Beetle mentioning
confidence: 99%
“…A relationship between the composition and production of oleoresin and water stress (Hodges and Lorio, 1975;Hodges et al, 1979; among others) may explain why oleoresin production is greater in thinned than unthinned loblolly pine stands (Brown et al, 1987). DeAngelis et al (1986) reported that age and rate of radial growth influenced the formation and development of radial resin ducts, which may explain why decreased radial tree growth and southern pine beetle infestations are correlated (Coulson et al, 1974). Hodges et al (1979) compared the chemical and physical properties of the oleoresin in four pine species, loblolly, shortleaf, P. echinata Mill., slash, P. elliottii Engelm., and longleaf pines, P. palustris Mill., and concluded there were differences in their relative susceptibility that were best explained by differences in resin flow characteristics.…”
Section: Tree and Stand Factors Associated With Southern Pine Beetle mentioning
confidence: 99%
“…As already mentioned, exhausting tree resistance can be completed in few days. However, tree death comes much later with disruption of water transportation, sapwood occlusion and fading of the foliage (DeAngelis et al, 1986;Nebeker et al, 1993;Lorio et al, 1995).…”
Section: Tissues Colonization and Tree Deathmentioning
confidence: 99%
“…One may thus wonder if tree resistance has really been completely exhausted at this time in the sapwood, or if fungi are really involved in tree death. Perhaps fungi can kill trees with toxins (DeAngelis et al, 1986;Hodges et al, 1989). Moreover, the presence of a certain area of blue stained sapwood in trees resisting beetle mass attacks or artificial mass inoculations with fungi demonstrates that colonization of tree tissues starts during the process of defense exhaustion.…”
Section: Tissues Colonization and Tree Deathmentioning
confidence: 99%
“…This is also supported by Mengistu et al (2012), who showed that resin production has a higher priority in carbon allocation than stem growth in B. papyrifera. In other studies, however, radial stem growth was positively correlated with the number of resin ducts in the bark of Picea glauca (Alfaro et al, 1997) and with the number of resin ducts in wood of P. taeda (DeAngelis et al, 1986), but negatively in another study in the wood of the same species (Blanche et al, 1992). Baier et al (2002), also reported negative relationship between radial stem growth and number of resin ducts in the secondary phloem of P. abies.…”
Section: Resin-canal and Tree Characteristicsmentioning
confidence: 77%
“…In addition to tree size, resin yield can also be directly related to characteristics of the resin-secretory structures that are responsible for the synthesis, storage and transport of resin (DeAngelis et al, 1986;Baier et al, 2002). Diameter of internal lumen of resin canals (hereafter diameter of resin canals), density of resin canals and number of epithelial cells are among the commonly mentioned characteristics of resin-secretory structures that determine resin yield (Blanche et al, 1992;Tolera et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%